1989
DOI: 10.2337/diab.38.6.704
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Effects of Long-Acting Somatostatin Analogue (Sandostatin) in Type I Diabetic Patients on Conventional Therapy

Abstract: We evaluated the effectiveness of a more potent and longer-acting somatostatin analogue (SMS 201-995) as an adjunct to insulin therapy, in a double-blind placebo-controlled randomized study of 26 C-peptide-negative type I (insulin-dependent) diabetic patients (20 women, 6 men, aged 22-40 yr) on their conventional drug regimens for 12 wk. Eight patients received a low dose (10 micrograms) of the analogue, 9 received a high dose (50 micrograms) of the analogue, and 9 received placebo subcutaneously before breakf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Administration of a long-acting somatostatin analog to people with type 1 diabetes over days to weeks has been reported to reduce glycemia in some (99) but not other (100,101) studies. However, it increases sensitivity to insulin (102,103), perhaps because of suppression of glucagon secretion.…”
Section: Relevance Of Glucagon To Hyperglycemia In Human Diabetesmentioning
confidence: 97%
“…Administration of a long-acting somatostatin analog to people with type 1 diabetes over days to weeks has been reported to reduce glycemia in some (99) but not other (100,101) studies. However, it increases sensitivity to insulin (102,103), perhaps because of suppression of glucagon secretion.…”
Section: Relevance Of Glucagon To Hyperglycemia In Human Diabetesmentioning
confidence: 97%
“…Ipp et al 27 reported that exogenous somatostatin impairs the clearance of exogenous insulin and therefore would reduce insulin requirements. However, a study by Osei et al 28 assessing the metabolic effects of sandostatin LAR on T1DM found no significant change in FPG, HbA1c or exogenous insulin requirements after 3 months of treatment with SSA in T1DM patients.…”
Section: Discussionmentioning
confidence: 97%
“…Ipp et al 27 reported that exogenous somatostatin impairs the clearance of exogenous insulin and therefore would reduce insulin requirements. However, a study by Osei et al 28 assessing the metabolic effects of sandostatin LAR…”
Section: Discussionmentioning
confidence: 99%
“…On the second occasion patients were treated with the somatostatin analogue octreotide which led to a marked suppression of ,-hydroxybutyrate, acetoacetate and (Grossmann et al, 1989;Osei et al, 1989;Spinas et al, 1985). Gerich et al (1975) previously published that continuous intravenous infusion of native somatostatin can prevent the development of ketoacidosis in type I diabetic patients, and specifically showed diminished or absent increments of P-hydroxybutyrate, FFA, glucose and glucagon levels.…”
Section: Discussionmentioning
confidence: 99%